Epstein-Barr virus induces fragmentation of chromosomal DNA during lytic infection. - Kawanishi, M (1993)
Pulsed-field agarose gel electrophoresis showed that fragmentation of chromosomal DNA in Raji cells was induced by infection with the P3HR-1 strain of Epstein-Barr virus (EBV). S1 nuclease treatment of the agarose plugs containing cells suggested that the majority of DNA fragments did not contain single-strand gaps. Chromosomal DNA fragmentation was inhibited by cycloheximide, indicating that protein synthesis was required for DNA fragmentation. Phosphonoacetic acid, an inhibitor of EBV DNA polymerase, did not inhibit fragmentation of chromosomal DNA. These findings suggest that EBV-specific early proteins participate in fragmentation of chromosomal DNA. Chromosomal DNA of P3HR-1 cells was also fragmented by treatment with n-butyrate plus 12-O-tetradecanoylphorbol-13-acetate (TPA), which induced activation of latent EBV genome following viral replication. In addition, fragmentation of DNA preceded cell death during lytic infection. These results suggest that fragmentation of chromosomal DNA is generally induced during EBV replication and probably contributes to the cytopathic effect of EBV. The role of DNA fragmentation in death of infected cells is discussed in relation to apoptosis.